Biomarker evidence for Botryococcus and a methane cycle in the Eocene Huadian oil shale, NE China. (January 2015) - Volkman, John K.; Zhang, Zhirong; Xie, Xiaomin; Qin, Jianzhong; Borjigin, Tenger
Highlights: The organic-rich Eocene Huadian oil shale contains abundant microalgal lipids. Isotopically depleted δ 13 C values for hop-17(21)-enes and neohopenes indicated methane oxidation. Biomarkers for the L race of Botryococcus, including lycopane, were identified. Abundant diasterenes and 4-methyldiasterenes indicated extensive lipid diagenesis. Abstract: The saturated and unsaturated hydrocarbons of two samples (HD-19 and HD-21) from the same section of the Middle Eocene lacustrine Huadian oil shale in NE China were identified and shown to be mainly from algal and bacterial sources. Comparison of the two samples provided an opportunity to explore the contribution from telalginite to the hydrocarbon profiles. Cells identified from microscopy as Botryococcus in the telalginite of HD-21 were confirmed as belonging to the L race of B. braunii from the presence of monoaromatic lycopane derivatives and small amounts of several lycopadienes. Lycopane was abundant and was probably derived from biohydrogenation of lycopadienes and related lipids on the basis of δ 13 C values. Hopane distributions showed a dominance of those with the biological 17β, 21β-stereochemistry, as expected for an immature shale, with low amounts of 17β, 21α-hopanes (moretanes) and 17α, 21β-hopanes. Two hopenes were also abundant and assigned as C29 and C30 neohop-13(18)-enes, which occurred together with the C29 and C30 hop-17(21)-enes. These had depleted carbon isotope values (−43.7‰ to −50.8‰), indicative of production by methane oxidizing bacteria (methanotrophs). The high proportion of hopanoids with carbon numbers < C32 indicates extensive post-depositional diagenetic alteration of bacteriohopanepolyols as well as a direct input of C30 hopanoids. The data clearly indicate that there was active utilization of methane in this lacustrine depositional setting, but isoprenoid hydrocarbon biomarkers for methanogens, such as pentamethylicosane (PMI) and squalane, were in surprisingly low abundance. It is possible that these bacterial contributions were present as polar lipids. The origins of an unusual C38 isoprenoid alkane assigned as bipristane are uncertain, but may be from methanogens. Steranes and sterenes were relatively minor components, but abundant diasterenes and 4-methyldiasterenes were present, reflecting significant conversion of the original lipid composition by way of clay-catalysed diagenesis. The biomarker data suggest that the bottom waters in the original depositional environment had low O2 content, but the sediments were probably neither sulfidic nor strongly reducing. The high content of organic matter in the shale likely reflects both high (but fluctuating) productivity due to eutrophic conditions in the overlying water and good preservation in the sediments.